PHYSICAL ACTIVITY OF UNIVERSITY STUDENTS AND ITS RELATION TO PHYSICAL FITNESS AND ACADEMIC SUCCESS - Silvester Lipošek; Jurij Planinšec; Bojan Leskošek; Aleksander Pajtler (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2019)
Introduction: The purpose of this study was to determine the physical activity performed by students, its frequency and intensity and how this physical activity may relate to their physical fitness and academic success. Methods: The sample consisted of 297 undergraduate students from 20 to 22 years of age (mean 20.5 ± 0.7) from the University of Maribor. The type and frequency of physical activity in which they engaged were measured using the IPAQ. Academic performance was defined as regular admission to the second year of study. Students' physical fitness was determined using Eurofit and FitnessGram tests. Results: Analysis of the IPAQ questionnaire shows that the majority of students reported being physically active in the afternoon. Nevertheless, according to the WHO's guidelines, 79.8 % of students were insufficiently physically active. The results show that males performed better than females in nearly all of the physical fitness tests. Periods of two to three hours of weekly physical activity were positively associated with academic success, while four hours or more resulted in no contribution. Conclusion: Correlations between physical activity and physical fitness were primarily found in higher duration physical activity and in higher frequency of vigorous exercise. The results of this study are similar to those of other countries regarding the insufficient physical activity of young people. The influence of physical activity on academic success was analyzed by binary logistic regression. The majority of students were academically successful and regularly admitted to the second year of study (86.5 %).